Consequences of an early catheter‐based intervention on pulmonary artery growth and right ventricular myocardial function in a pig model of pulmonary artery stenosis. Issue 1 (30th March 2018) - Bates, Melissa L.; Anagnostopoulos, Petros V.; Nygard, Cole; Torgeson, Jenna; Reichert, Jamie; Galambos, Csaba; Eldridge, Marlowe W.; Lamers, Luke J.
Abstract: Objective: To determine the consequences of an early catheter‐based intervention on pulmonary artery (PA) growth and right ventricular (RV) myocardial function in an animal model of branch PA stenosis. Background: Acute results and safety profiles of deliberate stent fracture within the pulmonary vasculature have been demonstrated. The long‐term impact of early stent intervention and deliberate stent fracture on PA growth and myocardial function is not understood. Methods: Implantation of small diameter stents was performed in a pig model of left PA stenosis at 6 weeks (10 kg) followed by dilations at 10 (35 kg) and 18 weeks (65 kg) with intent to fracture and implant large diameter stents. Hemodynamics, RV contractility, and 2D/3D angiography were performed with each intervention. The heart and pulmonary vasculature were histologically assessed. Results: Stent fracture occurred in 9/12 and implantation of large diameter stents was successful in 10/12 animals with no PA aneurysms or dissections. The final stented PA segment and distal left PA branch origins equaled the corresponding PA diameters of sham controls. Growth of left PA immediately beyond the stent was limited and there was diffuse fibro‐intimal proliferation within the distal left and right PA. RV contractility was diminished in the intervention group and the response to dobutamine occurred uniquely via increases in heart rate. Conclusions: Early stent intervention in this surgically created PA stenosis model was associated with improved growth of the distal PA vasculature but additional investigation of PA vessel physiology and impact on the developing heart are needed.